SOME IDEAS ON ACTUALIZATION OF TRANSDISCIPLINARY APPROACH IN UNIVERSITIES OF RUSSIA - T., Lappo (European Scientific Journal, ESJ, 2013)
The article deals with the problem of transdisciplinary approach implementation in the universities of the Russian Federation. Some definitions of the conceptual term `transdisciplinarity` are cited, the history of the term development is traced, examples of successful application of transdisciplinarity by Russian scientists are submitted. Although the trend to the transition to the transdisciplinary approach in science and educational techniques can be observed at present, the transdisciplinary approach hasn't yet got a mass character in Russia. Ordinary higher schools in the RF are facing a problem of realizing the necessity of such approach and development of necessary measures on transition to the principle of transdisciplinary approach in education and scientific research. Practical measures, which, in the author`s view, are to be taken by ordinary higher schools in order to pass on to the transdisciplinarity approach application in their scientific activities and educational process, are described.